Liberal values for South Asia - Wijesinha, Rajiva; Council for Liberal Democracy (Sri Lanka) (Colombo : Council for Liberal Democracy, 1997)
Contributed articles.
Keywords: Liberalism -- South Asia; South Asia -- Economic policy